Body size in Drosophila: Genetic architecture, allometries and sexual dimorphism - Carreira, V.P. (2009)
Even though substantial progress has been made to elucidate the physiological and environmental factors underpinning differences in body size, little is known about its genetic architecture. Furthermore, all animal species bear a specific relationship between the size of each organ and overall body size, so different body size traits should be investigated as well as their sexual dimorphism that may have an important impact on the evolution of body size. We have surveyed 191 co-isogenic lines of Drosophila melanogaster, each one of them homozygous for a single P-element insertion, and assessed the effects of mutations on different body size traits compared to the P-element-free co-isogenic control. Nearly 60% of the lines showed significant differences with respect to the control for these traits in one or both sexes and almost 35% showed trait- and sex-specific effects. Candidate gene mutations frequently increased body size in males and decreased it in females. Among the 92 genes identified, most are involved in development and/or metabolic processes and their molecular functions principally include protein-binding and nucleic acid-binding activities. Although several genes showed pleiotropic effects in relation to body size, few of them were involved in the expression of all traits in one or both sexes. These genes seem to be important for different aspects related to the general functioning of the organism. In general, our results indicate that the genetic architecture of body size traits involves a large fraction of the genome and is largely sex and trait specific. © 2009 Macmillan Publishers Limited All rights reserved.